1999
DOI: 10.1080/003655299750025697
|View full text |Cite
|
Sign up to set email alerts
|

Are There Changes in Gastric Emptying during the Menstrual Cycle?

Abstract: Evidence of postprandial 'physiologic gastroparesis' was found in women, although no differences were found between men and women in gastric motility during fasting. The rate of emptying was not related to changes in plasma concentrations of sex hormones during the menstrual cycle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…This finding may be of particular relevance to the current report of increased microparticle uptake during pregnancy, although the upward trend in uptake in the virgin female groups cannot yet be linked to hormonal differences, since the role of progesterone in gastrointestinal motility is still not clear (Caballero-Plasencia et al, 1999;Oh et al, 1998).…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…This finding may be of particular relevance to the current report of increased microparticle uptake during pregnancy, although the upward trend in uptake in the virgin female groups cannot yet be linked to hormonal differences, since the role of progesterone in gastrointestinal motility is still not clear (Caballero-Plasencia et al, 1999;Oh et al, 1998).…”
Section: Discussionmentioning
confidence: 49%
“…Motility disorders occur more often in women than in men (Ducker et al, 1996). Gastric emptying of digestive solids and liquids is slower in women than men (Caballero-Plasencia et al, 1999) but there is no link with the cyclical changes in plasma levels of sex hormones. Late pregnancy slows intestinal transit in rats, but does not alter gastric emptying (Chang et al, 1998) while the early lactation period is accompanied by an increase in both (Chen et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Other research suggests that while gastric emptying does appear to be more delayed in women than in men, this is not accounted for by the phases of the menstrual cycle or plasma concentrations of oestradiol or progesterone. [22][23][24] A systematic review has examined the relationship between HRQOL and functional dyspepsia. 15 It was concluded that the evidence that HRQOL is substantially affected by functional dyspepsia was remarkably limited despite the high prevalence and enormous cost of this condition.…”
Section: Discussionmentioning
confidence: 99%
“…Such complaints may not be explained by quantifiable physiologic changes in gastric function, which complicates their treatment by Western medicine. [15][16][17][18] An example of culture-specific symptoms is the feeling of coldness (hie). In our cases, hie was among the complaints of patient 3.…”
Section: Gepshtein Et Al 432mentioning
confidence: 99%